Whole Brain Mapping of Neurons Innervating Extraorbital Lacrimal Glands in Mice and Rats of Both Genders - Zhai, Ying; Li, Min; Gui, Zhu; Wang, Yeli; Hu, Ting; Liu, Yue; Xu, Fuqiang (Frontiers in Neural Circuits, 2021)
The extraorbital lacrimal glands (ELGs) secret tear to maintain a homeostatic environment for ocular surfaces, and pheromones to mediate social interactions. Although its distinct gender-related differences in mice and rats have been identified, its comprehensive histology of, together with whole-brain neuronal network remain largely unknown. The primary objective of present study is to investigate whether sex-specific differences take place in histological and physiological perspectives. Morphological and histological data were obtained via magnetic resonance imaging (MRI), hematoxylin-eosin (HE) staining in mice and rats of both genders. The innervating network were visualized by pseudorabies virus (PRV) mediated retrograde trans-multi-synaptic tracing system for adult C57BL6/J mice of both genders. In terms of ELGs’ anatomy, mice and rats across genders both have 7 main lobes, with one exception was observed in female rats which have only 5 lobes. Both female rats and mice generally have relatively smaller shape size, absolute weight, and cell size than males. Our viral tracing revealed a generally similar trend of innervating patterns antero-posteriorly, but significant gender differences also observed in the hypothalamus (HY), olfactory areas (OLF) and striatum (STR). Brain regions including piriform area (Pir), post-piriform transition area (TR), central amygdalar nucleus (CEA), medial amygdalar nucleus (MEA), lateral hypothalamic area (LHA), parasubthalamic nucleus (PSTN), pontin reticular nucleus (caudal part) (PRNc), and parabrachial nucleus, (PB) were commonly labelled. In addition, chemical isotope labelling-assisted liquid chromatography-mass spectrometry (CIL-LC-MS) and nuclear magnetic resonance spectroscopy (NMR spectroscopy) ways were performed to reveal fatty acids and metabolism of the ELGs reflecting the relationship between pheromone secretion and brain network. Overall, our results disclosed basic properties and the input neural networks for ELGs in both genders of mice, providing a structural basis to analyze the diverse functions of ELGs.